Glucocorticoids selectively inhibit translation of ribosomal protein mRNAs in P1798 lymphosarcoma cells. - Meyuhas, O (1987)
When P1798 murine lymphosarcoma cells are exposed to 10(-7) M dexamethasone, there is a dramatic inhibition of rRNA synthesis, which is completely reversible when the hormone is withdrawn. In the present experiments we examined whether dexamethasone treatment causes any alteration in the accumulation or utilization of mRNAs that encode ribosomal proteins (rp mRNAs). No effect on the accumulation of six different rp mRNAs was detected. However, the translation of five of six rp mRNAs was selectively inhibited in the presence of the hormone, as judged by a substantial decrease in ribosomal loading. Normal translation of rp mRNA was resumed within a few hours after hormone withdrawal. In untreated or fully recovered cells, the distribution of rp mRNAs between polyribosomes and free ribonucleoprotein is distinctly bimodal, suggesting that rp mRNAs are subject to a particular form of translational control in which they are either translationally inactive or fully loaded with ribosomes. A possible relationship between this mode of translational control and the selective suppression of rp mRNA translation by glucocorticoids is discussed.